2005
DOI: 10.1086/431999
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Detection and Localization of Maternally Acquired Human Cytomegalovirus in Placental Tissue by In Situ Polymerase Chain Reaction

Abstract: Transplacental transmission of human cytomegalovirus (CMV) can result in congenital malformations, although details on the mechanisms of transmission and the location of CMV in infected placentae need to be described.METHODS. Placental tissue from term (third trimester) deliveries was screened for CMV infection by polymerase chain reaction (PCR), in situ PCR (IS-PCR), and IS reverse-transcriptase PCR (IS RT-PCR).RESULTS. CMV DNA was detected in tissue samples from 11 placentae that had been determined to be ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Previous work with term placentas demonstrated the permissivity of purified trophoblasts for CMV infection, using the laboratory-adapted strain, AD169 (15). Syncytiotrophoblast infection was demonstrated in vivo in a study of thirdtrimester placenta, using in situ hybridization and PCR techniques (11). Another study of purified syncytiotrophoblast cultures demonstrated that these cells could be permissively infected with a number of laboratory-adapted strains of CMV, as with clinical isolates, although infection efficiencies differed amongst different strains (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work with term placentas demonstrated the permissivity of purified trophoblasts for CMV infection, using the laboratory-adapted strain, AD169 (15). Syncytiotrophoblast infection was demonstrated in vivo in a study of thirdtrimester placenta, using in situ hybridization and PCR techniques (11). Another study of purified syncytiotrophoblast cultures demonstrated that these cells could be permissively infected with a number of laboratory-adapted strains of CMV, as with clinical isolates, although infection efficiencies differed amongst different strains (18).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to serving as a gateway to the fetus, the placenta may be directly injured by CMV, conceivably leading to intrauterine growth retardation and fetal disease (7-10). Thus, study of CMV placental infection may facilitate improved understanding of these potentially diverse mechanisms of viral-mediated fetal injury.A number of reports have identified CMV in placental tissue from clinical samples (11)(12)(13)(14). Several in vitro models for studying CMV-placental interactions have also been developed (15-20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These cells build a bridge at the fetal-maternal interface and can be efficiently infected by HCMV in vitro and in vivo (10,(43)(44)(45)(46). In addition, infection of CTB in early gestation often results in placental developmental abnormalities (44,(46)(47)(48).…”
mentioning
confidence: 99%
“…Indeed, HCMV DNA and gene expression has been found in clinical samples taken from placentas early and late in gestation (45,50,54,68). Accumulating experimental and clinical evidence indicates that, in addition to serving in viral transmission, the placenta may be actively injured by HCMV, conceivably contributing to the observed IUGR and fetal disease (1,50,59,60).…”
mentioning
confidence: 99%